Extracts of Bridelia ovata and Croton oblongifolius induce apoptosis in human MDA-MB-231 breast cancer cells via oxidative stress and mitochondrial pathways - Juthathip Poofery (2020)
© 2020 Spandidos Publications. All rights reserved. Breast cancer is the most common type of cancer and is also the second leading cause of cancer-associated death in women worldwide. Thus, there is an urgent requirement for the development of effective treatments for this disease. Bridelia ovata and Croton oblongifolius are herbs used in Thai traditional medicine that have been used to treat various health problems; B. ovata has traditionally been used as a purgative, an antipyretic, a leukorrhea treatment and as a birth control herb. C. oblongifolius has been used to increase breast milk production, for post-partum care (where it is used as a hot bath herb), and as a treatment for flat worms and dysmenorrhea. However, there is little research investigating the anticancer properties of these herbs. The present study aimed to investigate the anticancer properties of crude ethyl acetate extracts of B. ovata (BEA) and C. oblongifolius (CEA) in order to explore their underlying mechanisms in breast cancer cell death. The phytoconstituents of the crude extracts of BEA and CEA were studied using gas chromatography-mass spectrometry (GC-MS). GC-MS analysis showed that the primary compound in BEA is friedelan-3-one, and kaur-16-en-18-oic acid in CEA. Cytotoxicity was investigated using an MTT assay, both BEA and CEA showed greater toxicity against MDA-MB-231 breast cancer cells compared with their effect on MCF10A normal epithelial mammary cells. BEA and CEA exerted various effects, including inducing apoptotic cell death, reducing mitochondrial transmembrane potential, increasing the levels of intracellular ROS, activating caspases, upregulating pro-apoptotic and downregulating anti-apoptotic genes and proteins. BEA and CEA were shown to have anticancer activity against breast cancer cells and induce apoptosis in these cells via a mitochondrial pathway and oxidative stress.